NUCLEAR ENERGY SAFETY: MODERN TRENDS AND TECHNOLOGICAL APPROACHES (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The study focuses on contemporary trends and technological solutions aimed at enhancing nuclear energy safety. It reviews recent advancements in reactor engineering, digital protection systems, and risk assessment techniques designed to prevent accidents and reduce environmental risks. Particular emphasis is placed on passive safety mechanisms, next-generation small modular reactors (SMRs), and the use of artificial intelligence for predictive maintenance and rapid emergency response. Additionally, the research underscores the significance of international safety standards and regulatory frameworks in guiding the development of the nuclear sector. Ultimately, the work highlights how technological progress and global collaboration are essential for building a safe and sustainable nuclear energy future.